Monovalent antibodies against MM-creatine kinase remove the M line from myofibrils. - Wallimann, T (1978)
Column-purified antibodies against creatine kinase (EC 2.7.3.2) from chicken skeletal muscle (the homodimeric isoenzyme designated MM-CK) bind specifically to the M lines of chicken pectoral muscle myofibrils. Incubation of myofibrils with monovalent Fab' fragments of these antibodies solubilizes most of the myofibril-bound creatine kinase, concomitantly removing most of the electron-dense material from the M lines. This strongly indicates that MM-CK is an integral part of the M-line structure and is consistent with the suggestion that MM-CK molecules form the M bridges that are responsible for the principle M-line substriations.